1994
DOI: 10.1001/archinte.1994.00420230086010
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Fluticasone Propionate Is More Effective Than Terfenadine Tablets for Seasonal Allergic Rhinitis

Abstract: Fluticasone aqueous nasal spray, a well-tolerated corticosteroid preparation that can be administered once daily, is more effective than terfenadine tablets or placebo in controlling symptoms of seasonal allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…Due to the possible flushing action of unmedicated spray on the nasal passages, there may be a beneficial effect of the vehicle placebo spray on nasal symptoms, and in turn on ocular symptoms, as secretions containing mediators and inflammatory cells are removed from the nose [20,27,28]. Similar to the findings of this study, other allergic rhinitis studies have shown non-sedating oral antihistamines to be no more effective than vehicle placebo aqueous nasal spray [20,29,30].…”
Section: Discussionsupporting
confidence: 54%
“…Due to the possible flushing action of unmedicated spray on the nasal passages, there may be a beneficial effect of the vehicle placebo spray on nasal symptoms, and in turn on ocular symptoms, as secretions containing mediators and inflammatory cells are removed from the nose [20,27,28]. Similar to the findings of this study, other allergic rhinitis studies have shown non-sedating oral antihistamines to be no more effective than vehicle placebo aqueous nasal spray [20,29,30].…”
Section: Discussionsupporting
confidence: 54%
“…In the USA, a similar study was conducted comparing FPANS (200JIg once daily) with terfenadine (60mg twice daily) and placebo in 230 patients with allergic rhinitis to Mountain Cedar. Results showed FPANS had superior efficacy over terfenadine for total nasal symptom scores (obstruction, rhinorrhoea, sneezing and itching) [8].…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have demonstrated that FPANS given as a once daily 200 J-Lg dose is an effective treatment for seasonal allergic rhinitis [7][8][9][10][11]. Oral administration of a twice daily 60 mg dose of terfenadine, a commonly used H I-receptor antagonist, has been favourably compared with placebo in the treatment of seasonal allergic rhinitis and conjunctivitis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Methods of concealing allocation to the treatment arms were identified and classified according to the criteria of the Cochrane Collaboration9: A, adequate; B, allocation method unclear; and C, inadequate. Two studies were classified as A 13 19 and the remainder were classified as B.…”
Section: Methodsmentioning
confidence: 99%